Optimization of Drilling Path Using the Bees Algorithm - Kamaruddin, Shafie; Naqiuddin Rosdi, Mohamad; Aiman Sukindar, Nor (Manufacturing Technology Journal, 2022)
Optimization is the process of finding the best possible solutions of a problem. It has been widely used in various areas especially in engineering problems. One of the common issues that is faced by some of manufacturers is finding drilling sequences of multiple holes. By drilling multiple holes with the least total path length, the manufacturer can save a lot of time and it can increase the productivity of the company. Thus, this study focuses on drilling path of multiple holes problem which has been solved by other researchers. This study uses the Bees Algorithm to find the best sequence of drilling holes (mini-mum total path length) and the results found are compared with the result of other algorithms. In addi-tion to results comparison with other algorithms, the results obtained are verified with simulation results using MasterCAM software. The results comparison shows that the Bees Algorithm achieved compara-ble performance compared to other algorithms.
Keywords: Bees Algorithm; Optimization; Drilling